Mechanisms for Bridging the Digital Divide in International Experiences: Solutions to Enhance E-Governance in Egypt - Sharawy, Nahed Hamouda; Barakat, Khaled (The Arab Journal of Administration, 2025)
The purpose of this paper is to investigate the role of mechanisms bridging the digital divide (DD) with the three dimensions technology, knowledge, and electronics, in order to improve e-governance. The paper focuses on e-services, transparency, participation, and accountability in international experiences, mainly concerning the achievement of the SDGs, to propose solutions for Egypt and other developing countries. Design/methodology/approach- This study merges a comparative analysis methodology with a descriptive-analytical approach to compare four country studies: the UK as a developed country; China and India as developing countries; and UAE as an Arab country, according to determined study standards. The study uses secondary data sources from international reports, and theoretical literature, as well as preliminary data from digital strategies, and state documents published in each the country’s e-portals. Finding- This study examines similarities and differences in standards compliance in four countries, namely UK, China, India, and the UAE, indicating the role of a positive relationship between the mechanisms for bridging DD and the promotion of e-governance. Originality/value- To the best of the authors’ knowledge, this is one of the few studies that investigate the relationship between mechanisms of bridging DD, and enhancing e-governance on the international level. This study creates a crucial contribution as it demonstrates the significance of applying e-governance in governmental institutions in general, and particularly in Egypt as a leading model, being a critical country in Africa and the Middle East.